Sustainability of the hookah diving fishery in Turkey - Uğur Karadurmuş; Mehmet Aydın (Journal of Fisheries, 2023)
Hookah diving is a traditional fishing method based on the hand collection of commercial benthic organisms. Fishers continue their profession without paying attention to their physical health and psychophysical fitness. Ignoring the diving safety and decompression rules underwater, using improvised diving systems, and economic concerns carry risks that can result in death. The long-term sustainability of work depends on nations’ ability to control fishing practices and promote good management. This study discusses the current situation of hookah divers in Turkey based on official statistics from the ministry and face-to-face interviews with hookah divers. The data were subjected to strengths, weaknesses, opportunities, and threats (SWOT) analysis and synthesised with the literature for strategic analysis. The sector’s contribution to the national economy, economic satisfaction of divers, and supporting rural employment were evaluated as strengths. Lack of expertise in the professional career and complex laws were identified as threats that require urgent solutions. Multidirectional national efforts are needed for sustainable fishing, including stakeholder networking, diving safety, hookah equipment, underwater fishing strategies, training curricula and professional career development. Our findings offer strategic and planning approaches for the sustainable development of hookah diving in Turkey.